Language Politeness of Local Tour Guides in Orangutan Ecotourism Bukit Lawang, North Sumatra: A Sociopragmatic Study - Taulia, Taulia; Gapur, Abdul; Pujiono, Mhd. (Soegijapranata Catholic University, 2023)
Bukit Lawang is a conservation area for orangutans located in North Sumatra, Indonesia. This research aims to examine the politeness markers used by tour guides in this area. The qualitative research method with a phenomenological approach was employed. Data were collected through observation, field notes, audio video recordings, and interviews. The findings indicate that tour guides in Bukit Lawang utilize various politeness markers, including offering assistance, expressing agreement, making requests, giving commands, refusing, apologizing, providing advice, and giving compliments. Local tour guides in Bukit Lawang also employ diverse non-verbal politeness markers, such as smiling, in their interactions with tourists. Factors influencing the use of these language politeness markers include social harmony, the desire to please tourists, social and cultural norms, professionalism, and public image. In conclusion, this study provides a better understanding of the use of language politeness markers by tour guides in Bukit Lawang Orangutan Ecotourism. The research findings can serve as a basis for enhancing tourism services and enriching knowledge about cross-cultural interactions in the context of tourism.